Efficiency of using Dupont Ratio and its Components to Forecast the Changes in Future Profitability - Mohammad Arabmazar Yazdi (Shahid Bahonar University of Kerman, 2011)
This study attempts to evaluate whether adjusted Dupont ratio can have better prediction of future profitability (Return on Net Operating Asset) or decomposition of adjusted Dupont ratio to its components (net operating asset turnover and operating profit margin) can have better prediction of future profitability. Finally, it was examined if decomposition of changes in adjusted Dupont ratio - changes in net operating asset turnover and changes in operating profit margin- can enhance prediction of future profitability in one year ahead. Results which were based on panel analysis and for period from 2000 to 2009 showed that decomposition of the adjusted Dupont ratio level to its components is not able to improve future profitability prediction, while decomposition of changes in adjusted Dupont ratio can enhance prediction of profitability in one year ahead. Furthermore, changes in the net operating asset turnover have better ability (in comparison with operating profit margin) to predict future profitability.